Solar cell and method for manufacturing the same
By dissolving small molecules coordinated with lead ions in the hole transport layer, the challenges of perovskite-hole interface morphology and defect manipulation are solved, and the wetting properties of the perovskite absorber layer and the performance and stability of the solar cell are improved.
Patent Information
- Application Number
- CN202311294891.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-08
- Publication Date
- 2025-04-08
AI Technical Summary
Manipulating morphology and defects at the perovskite-hole interface is more challenging, especially in the case of trans-structured PSCs, resulting in a reduced radiation efficiency of the perovskite absorber layer and an increased overall non-radiative recombination loss.
The small molecules coordinated with lead ions are dissolved in the hole transport layer, such as small molecules containing phosphine oxide groups, sulfone moieties or carbonyl groups, thereby enhancing the binding force between the hole transport layer and the perovskite absorber layer.
By enhancing the binding force between the hole transport layer and the perovskite absorber layer, the wetting ability of the perovskite precursor solution is improved, and the performance and long-term stability of solar cells are improved.
Smart Images

Figure CN119789746A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solar cells, and in particular to solar cells and methods for preparing the same. Background Art
[0002] Perovskite materials have attracted extensive attention in the past decade due to their tunable band gap, strong absorption coefficient, high carrier mobility and long carrier lifetime. The power conversion efficiency (PCEs) of perovskite solar cells (PSCs) has exceeded 30%. Perovskite combined with crystalline silicon can form a stacked cell structure with a maximum photoelectric conversion efficiency of 33.7%, far exceeding the theoretical efficiency limit of single crystalline silicon cells, and has great application potential and development space. Further improving the performance and stability of PSCs requires delicate management of the interface between the perovskite absorption layer and the charge transport layer. Through in-depth research on the bottom surface of the perovskite film and its interface with the charge transport layer, the PCEs of the formal (nip) and trans (pin) structures have been continuously improved. However, it is more challenging to manipulate the morphology and defects at the perovskite-hole interface, especially in the case of trans-structured PCEs.
[0003] In the inverse PSCs structure, perovskite is deposited on a hole transport layer, which plays an important role in perovskite nucleation and heterojunction formation. HTL (hole transport layer) usually uses materials such as polytriarylamine (PTAA), Poly-TPD, PEDOT:PSS, etc., but is too hydrophobic for the perovskite precursor solution or is chemically unstable when it comes into contact with the perovskite. Both factors can produce morphological, compositional or electronic defects at the buried perovskite substrate interface, thereby limiting photovoltaic performance and stability. In most cases, HTL reduces the radiative efficiency of the perovskite absorber layer and increases the overall non-radiative recombination losses, so further improvements in HTL are needed to support high-quality perovskite deposition and reduce the density of nanopores and deep-seated electronic defects buried at the interface.
[0004] In view of this, this application is hereby filed. Summary of the invention
[0005] The purpose of the present application is to provide a solar cell and a method for preparing the same, aiming to improve at least one of the problems mentioned in the background technology.
[0006] In a first aspect, the present application provides a method for preparing a solar cell, comprising:
[0007] coating a hole transport layer solution on a substrate to form a hole transport layer,
[0008] A perovskite layer solution is coated on the hole transport layer, wherein the perovskite layer solution contains lead ions;
[0009] Small molecules coordinated with lead ions are dissolved in the hole transport layer solution.
[0010] In an optional embodiment, the small molecule coordinated with the lead ion dissolved in the hole transport layer solution is a small molecule containing a phosphine oxide group, a small molecule containing a sulfone moiety, or a small molecule containing a carbonyl group.
[0011] In an optional embodiment, the small molecule containing a phosphine oxide group is selected from at least one of trimethylphosphine oxide, triethylphosphine oxide, tripropylphosphine oxide, tributylphosphine oxide, triylpentylphosphine oxide, trihexylphosphine oxide, triheptylphosphine oxide, trioctylphosphine oxide, diphenylphosphine oxide, triphenylphosphine oxide, ethyldiphenylphosphine oxide, di-tert-butylphosphine oxide and tripyrrolidinephosphine oxide;
[0012] In an optional embodiment, the small molecule containing a sulfone unit is selected from at least one of butyl sulfone, diphenyl sulfone, dimethyl sulfone, butyl sulfoxide, benzyl sulfone, methyl vinyl sulfone, ethyl phenyl sulfone, phenyl vinyl sulfone, methyl phenyl sulfoxide, methyl ethyl sulfone, ethyl vinyl sulfone, dodecyl methyl sulfoxide, methyl p-toluene sulfoxide, 4-aminophenyl sulfone, bis(4-chlorophenyl) sulfone and 4,4'-ditoluene sulfoxide.
[0013] In an optional embodiment, the small molecule containing a carbonyl group is selected from at least one of 1,1′-carbonyldiimidazole, 1,1′-carbonylbis(1,2,4-triazole), N-cyanocarbonyldiphenyl ester, 4-ethoxycarbonylphenyl isocyanate, 2-(methoxycarbonyl)phenyl isocyanate, ethoxycarbonyl isothiocyanate, 1,1′-thiocarbonyldi-2(1H)-pyridone, and 1,1'-(azodicarbonyl)dipiperidine.
[0014] In an optional embodiment, the small molecule containing a phosphine oxide group is triethylphosphine oxide, and the mass ratio of triethylphosphine oxide to the hole transport layer material is 1:50-1:5.
[0015] In an optional embodiment, a hole transport layer solution is coated on a substrate, and a two-step annealing and drying process is performed to form a hole transport layer;
[0016] The two-step annealing method is to place the substrate coated with the hole transport layer solution at a temperature of 50-60° C. for drying for 3-5 minutes, and then place it at a temperature of 100-110° C. for drying for 10-15 minutes.
[0017] In an optional embodiment, the solar cell is a tandem cell or a single junction cell;
[0018] In an optional embodiment, the hole transport layer solution further includes a high boiling point solvent.
[0019] In an optional embodiment, the high boiling point solvent is selected from at least one of dimethylacetamide, aniline, bromobenzene, o-dichlorobenzene and butyl butyrate, PC (propylene carbonate), and E-CPL (E-caprolactone).
[0020] In a second aspect, an embodiment of the present application provides a solar cell, which is manufactured using the manufacturing method provided in any embodiment of the present application.
[0021] The preparation method provided by the present application can enhance the binding force between the hole transport layer and the perovskite light absorbing layer, thereby achieving the effect of enhancing the long-term stability of the device, and can improve the wettability of the perovskite precursor solution on the surface of the hole transport layer, so that the solar cell has a higher quality perovskite light absorbing layer. Therefore, the solar cell prepared by the preparation method provided by the embodiment of the present application can have better performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 A schematic diagram of the structure of a solar cell according to an embodiment of the present application;
[0024] Figure 2 A comparison chart of the open circuit voltage test results of the solar cell prepared by testing the standard component and Example 1;
[0025] Figure 3 A comparison chart of current density test results of a solar cell prepared by testing a standard component and Example 1;
[0026] Figure 4 The figure is a comparison chart of the test results of the photoelectric conversion efficiency of the solar cell made by the test standard part and Example 1;
[0027] Figure 5 This is a comparison chart of the filling factor test results of the stacked solar cell made by the test standard component and Example 1;
[0028] Figure 6 is the contact angle of the perovskite precursor solution dropped on the hole transport layer made from solution A;
[0029] Figure 7 is the contact angle of the perovskite precursor solution dropped on the hole transport layer made from solution B. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0031] The solar cell and the method for preparing the solar cell provided in the embodiments of the present application are described in detail below.
[0032] The method for preparing a solar cell provided in an embodiment of the present application comprises:
[0033] coating a hole transport layer solution on a substrate to form a hole transport layer,
[0034] A perovskite layer solution is coated on the hole transport layer, wherein the perovskite layer solution contains lead ions;
[0035] Small molecules coordinated with lead ions are dissolved in the hole transport layer solution.
[0036] The preparation method provided in the embodiment of the present application can enhance the binding force between the hole transport layer and the perovskite light absorption layer due to the distribution of small molecules coordinated with lead ions in the hole transport layer, thereby achieving the effect of enhancing the long-term stability of the device. In addition, the wettability of the perovskite precursor solution on the surface of the hole transport layer can be improved, so that the solar cell has a higher quality perovskite light absorption layer. Therefore, the solar cell prepared by the preparation method provided in the embodiment of the present application can have better performance.
[0037] Furthermore, a portion of high-boiling-point solvent is selectively added to the hole transport layer solution to delay the drying process, thereby inducing the phosphine oxide groups or sulfone moieties or carbonyl small molecules in the film layer to achieve efficient coordination with the perovskite film layer;
[0038] The preparation method is specifically as follows:
[0039] S1. Prepare solution
[0040] 1. Prepare hole transport layer solution:
[0041] The components of the hole transport layer solution are mixed evenly. The components include a main solvent, a hole transport material, and small molecules coordinated with lead ions. The main solvent is a solvent for dissolving the hole transport material.
[0042] Specifically, the main solvent is selected from at least one of chlorobenzene and toluene.
[0043] Optionally, the small molecule coordinated with the lead ion is a small molecule containing a phosphine oxide group or a small molecule containing a sulfone moiety or a small molecule containing a carbonyl group.
[0044] Preferably, the small molecule containing a phosphine oxide group is selected from at least one of trimethylphosphine oxide, ethylphosphine oxide, tripropylphosphine oxide, tributylphosphine oxide, triylpentylphosphine oxide, trihexylphosphine oxide, triheptylphosphine oxide, trioctylphosphine oxide, diphenylphosphine oxide, triphenylphosphine oxide, ethyldiphenylphosphine oxide, di-tert-butylphosphine oxide and tripyrrolidinephosphine oxide;
[0045] Optionally, the small molecule containing a phosphine oxide group is triethylphosphine oxide, and the mass ratio of triethylphosphine oxide to the hole transport layer material is 1:50-1:5.
[0046] Optionally, the small molecule containing sulfone units is selected from at least one of butyl sulfone, diphenyl sulfone, dimethyl sulfone, butyl sulfoxide, benzyl sulfone, methyl vinyl sulfone, ethyl phenyl sulfone, phenyl vinyl sulfone, methyl phenyl sulfoxide, methyl ethyl sulfone, ethyl vinyl sulfone, dodecyl methyl sulfoxide, methyl p-toluene sulfoxide, 4-aminophenyl sulfone, bis(4-chlorophenyl) sulfone and 4,4'-ditoluene sulfoxide.
[0047] Optionally, the small molecule containing a carbonyl group is selected from at least one of 1,1′-carbonyldiimidazole, 1,1′-carbonylbis(1,2,4-triazole), N-cyanocarbonyldiphenyl ester, 4-ethoxycarbonylphenyl isocyanate, 2-(methoxycarbonyl)phenyl isocyanate, ethoxycarbonyl isothiocyanate, 1,1′-thiocarbonyldi-2(1H)-pyridone, and 1,1'-(azodicarbonyl)dipiperidine.
[0048] Alternatively, the hole transport material includes Poly-TPD (poly[bis(4-phenyl)(4-butylphenyl)amine]; 4-butyl-N,N-diphenylaniline homopolymer) and PTAA (poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]).
[0049] In some embodiments, the components may further include a high boiling point solvent. Adding a high boiling point solvent miscible with the main solvent can delay the drying rate and achieve strong coordination with lead ions.
[0050] Optionally, the high boiling point solvent is selected from at least one of dimethylacetamide, aniline, bromobenzene, o-dichlorobenzene and butyl butyrate.
[0051] 2. Prepare perovskite precursor solution:
[0052] The components of the perovskite precursor solution are mixed evenly. These components include PbCl2, CsI, PbBr2 and FAI (formamidine hydroiodide) for generating the target perovskite molecules, MACl (methylamine chloride) for inducing the formation of perovskite molecules, and solvent. The solvent is a mixture of DMF (dimethylformamide) and DMSO (dimethyl sulfoxide) in a volume ratio of 4:1.
[0053] In addition to the above-mentioned preparation methods, other existing perovskite precursor solutions containing lead ions in the field of solar cells can also be used in the present application.
[0054] S2. Formation of hole transport layer
[0055] The hole transport layer solution is spin-coated on a clean substrate, and then the silicon wafer on which the hole transport layer solution is spin-coated is annealed and dried to obtain the hole transport layer.
[0056] Specifically, the spin coating speed may be, for example, 5000 rpm and the time may be 15 s.
[0057] Preferably, the annealing and drying treatment is carried out as follows: the substrate coated with the hole transport layer solution is placed at a temperature of 50 to 60°C (e.g., 50°C, 55°C or 60°C) and dried for 3 to 5 minutes (e.g., 3 minutes, 4 minutes or 5 minutes), and then placed at a temperature of 100 to 110°C (e.g., 100°C, 105°C or 110°C) and dried for 10 to 15 minutes (e.g., 10 minutes, 12 minutes or 15 minutes).
[0058] The above-mentioned annealing method is a two-step low-temperature annealing, which delays the drying process and can further induce the small molecules in the film layer and the perovskite light-absorbing layer to achieve efficient coordination.
[0059] Alternatively, if Figure 1 As shown, Figure 1 From bottom to top, there are substrate, hole transport layer, perovskite light absorption layer, electron transport layer, buffer layer, and metal electrode layer.
[0060] By adding small molecules coordinated with lead ions to the hole transport layer, a good effect is achieved. The principle is that the hole transport layer based on the addition of small molecules of phosphine oxide groups or sulfone moieties or carbonyl groups can provide a targeted effect, which can enable the perovskite layer to achieve a good deposition on the hole transport layer with a targeted target, and the connection between the film layers is tighter. Then the overall film quality and film stability are improved. The inventors found that a layer of modification layer is often required between the existing hole transport layer and the perovskite layer to meet the electrical effect, but the solution of adding the above-mentioned small molecules to the hole transport layer of the present application can achieve the effect of removing the modification layer. While improving the effects of wettability and stability, it can also reduce a layer of modification layer, thereby reducing the process steps, improving the process efficiency, and saving costs.
[0061] Optionally, the small molecule containing a phosphine oxide group is selected from at least one of triethylphosphine oxide, tripropylphosphine oxide, tributylphosphine oxide, triylpentylphosphine oxide, trihexylphosphine oxide, triheptylphosphine oxide, trioctylphosphine oxide, diphenylphosphine oxide, triphenylphosphine oxide, ethyldiphenylphosphine oxide, di-tert-butylphosphine oxide and tripyrrolidinephosphine oxide;
[0062] Optionally, the small molecule containing sulfone units is selected from at least one of butyl sulfone, diphenyl sulfone, dimethyl sulfone, butyl sulfoxide, benzyl sulfone, methyl vinyl sulfone, ethyl phenyl sulfone, phenyl vinyl sulfone, methyl phenyl sulfoxide, methyl ethyl sulfone, ethyl vinyl sulfone, dodecyl methyl sulfoxide, methyl p-toluene sulfoxide, 4-aminophenyl sulfone, bis(4-chlorophenyl) sulfone and 4,4'-ditoluene sulfoxide.
[0063] Optionally, the small molecule containing a carbonyl group is selected from at least one of 1,1′-carbonyldiimidazole, 1,1′-carbonylbis(1,2,4-triazole), N-cyanocarbonyldiphenyl ester, 4-ethoxycarbonylphenyl isocyanate, 2-(methoxycarbonyl)phenyl isocyanate, ethoxycarbonyl isothiocyanate, 1,1′-thiocarbonyldi-2(1H)-pyridone, and 1,1'-(azodicarbonyl)dipiperidine.
[0064] Alternatively, the hole transport material includes Poly-TPD (poly[bis(4-phenyl)(4-butylphenyl)amine]; 4-butyl-N,N-diphenylaniline homopolymer) and PTAA (poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]).
[0065] S3. Formation of perovskite light-absorbing layer
[0066] The perovskite precursor solution is spin-coated on the hole transport layer and then annealed and dried to form the perovskite light absorbing layer.
[0067] Specifically, the spin coating method may be, for example, firstly spin coating at a low rotation speed of 300 rpm for 5 seconds to spread the solution, and then spin coating at a rotation speed of 3500 rpm for 10 seconds to spread the solution evenly.
[0068] Furthermore, the annealing and drying temperature may be, for example, 120° C. and the time may be 20 min.
[0069] S4. Formation of electron transport layer
[0070] C is evaporated on the perovskite light absorbing layer 60 , and obtain an electron transport layer.
[0071] It should be noted that the materials of the electron transport layer are 60 In addition, other existing electron transport layer materials can also be applied in this application.
[0072] S5. Formation of buffer layer
[0073] A buffer layer is deposited on the electron transport layer.
[0074] Specifically, the material of the buffer layer may be, for example, SnO 2 , and other existing electron transport layer materials may also be applied to the present application.
[0075] S6. Formation of transparent electrode
[0076] A transparent electrode is formed on the buffer layer.
[0077] Specifically, the material of the transparent electrode may be, for example, IZO (indium zinc oxide).
[0078] S7. Formation of metal electrode layer
[0079] A thick metal electrode layer is evaporated on the transparent electrode layer.
[0080] Specifically, the material of the metal electrode layer may be copper or silver or a mixture of copper and silver.
[0081] In a stacked cell, the metal electrode layer cannot cover the effective area, but it must be in contact with the effective area to conduct the circuit, so a transparent electrode layer is needed to connect it. However, the transparent electrode can easily break through the electron transport layer when sputtering, so a buffer layer is needed to protect the electron transport layer. The anti-reflection layer is to reduce the reflection of light and absorb more light.
[0082] In a single-junction battery, the metal electrode layer covers the effective area, but light is incident from the back, which is a glass surface, so there is no light loss. In addition, the metal electrode layer is not light-transmissive. When light enters and hits the electrode metal, it can be absorbed again. Therefore, a single-junction battery does not need a buffer layer or an anti-reflection layer.
[0083] The solar cell provided in the embodiment of the present application is manufactured using the manufacturing method provided in the present application.
[0084] It should be noted that in the production of normal perovskite single-junction cells or stacked cells, since an electron transport layer is first formed on the substrate, optionally, when the small molecules coordinated with lead ions dissolved in the electron transport layer solution are small molecules with phosphine oxide groups, sulfone moieties or carbonyl groups, the wettability of the perovskite light-absorbing layer can be further improved, thereby improving device performance.
[0085] Optionally, the small molecule containing a phosphine oxide group is selected from at least one of triethylphosphine oxide, tripropylphosphine oxide, tributylphosphine oxide, triylpentylphosphine oxide, trihexylphosphine oxide, triheptylphosphine oxide, trioctylphosphine oxide, diphenylphosphine oxide, triphenylphosphine oxide, ethyldiphenylphosphine oxide, di-tert-butylphosphine oxide and tripyrrolidinephosphine oxide;
[0086] Optionally, the small molecule containing sulfone units is selected from at least one of butyl sulfone, diphenyl sulfone, dimethyl sulfone, butyl sulfoxide, benzyl sulfone, methyl vinyl sulfone, ethyl phenyl sulfone, phenyl vinyl sulfone, methyl phenyl sulfoxide, methyl ethyl sulfone, ethyl vinyl sulfone, dodecyl methyl sulfoxide, methyl p-toluene sulfoxide, 4-aminophenyl sulfone, bis(4-chlorophenyl) sulfone and 4,4'-ditoluene sulfoxide.
[0087] Optionally, the small molecule containing a carbonyl group is selected from at least one of 1,1′-carbonyldiimidazole, 1,1′-carbonylbis(1,2,4-triazole), N-cyanocarbonyldiphenyl ester, 4-ethoxycarbonylphenyl isocyanate, 2-(methoxycarbonyl)phenyl isocyanate, ethoxycarbonyl isothiocyanate, 1,1′-thiocarbonyldi-2(1H)-pyridone, and 1,1'-(azodicarbonyl)dipiperidine.
[0088] The electron transport layer is formed by a person skilled in the art using a solution method to prepare the electron transport layer. The remaining steps for preparing the upright device are not described in detail.
[0089] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0090] Example 1
[0091] Prepare hole transport layer solution:
[0092] A chlorobenzene solution of Poly-TPD with a concentration of 4 mg / ml and a chlorobenzene solution of PTAA with a concentration of 4 mg / ml were mixed for later use, and the solution was marked as solution A. Trioctylphosphine oxide was dissolved in solution A, and the solution was marked as solution B, wherein the concentration of trioctylphosphine oxide was 0.8 mg / ml;
[0093] Prepare perovskite precursor solution:
[0094] MACl, PbCl2, CsI, PbBr2, and FAI were dissolved in a mixed solution of DMF and DMSO with a volume ratio of 4:1, and stirred at 50°C for two hours for later use;
[0095] Solution B was spin-coated on a clean silicon wafer at a rotation speed of 5000 rpm for 15 seconds, and then the silicon wafer after spin-coating with solution B was dried at 60°C for 5 minutes, and then placed at a temperature of 100°C for 10 minutes to obtain a hole transport layer;
[0096] The perovskite precursor solution was spin-coated on the hole transport layer at a rotation speed of 300 rpm and 3500 rpm for 5 s and 10 s respectively, and then the silicon wafer spin-coated with the perovskite precursor solution was annealed at 120°C for 20 min, finally forming a perovskite light absorption layer on the hole transport layer;
[0097] Evaporation thickness C60 , and get C 60 Electron transport layer;
[0098] In C 60 Atomic deposition of SnO2 on the electron transport layer to obtain a SnO2 buffer layer;
[0099] IZO is sputtered on the SnO2 buffer layer to obtain an IZO transparent electrode;
[0100] Cu is evaporated on the IZO transparent electrode to obtain a metal electrode layer, thus obtaining a solar tandem cell.
[0101] Example 2
[0102] This embodiment has the same and different aspects as Embodiment 1, and the same aspects will not be repeated here. The difference is that:
[0103] The substrate used is conductive glass;
[0104] C 60 The thickness of the electron transport layer and the evaporated C 60 The layers after the electron transport layer are different from those in Example 1. The thickness of this part is the difference between the thickness of stacked and single-junction perovskite cells made by technicians in this field, and will not be repeated here.
[0105] Evaporation C 60 After the electron transport layer, in C 60 A barrier layer is evaporated on the electron transport layer; and a copper electrode layer is evaporated on the barrier layer.
[0106] Example 3
[0107] The similarities between Example 3 and Example 1 are not repeated here. The difference between Example 3 and Example 1 is that trioctylphosphine oxide is replaced by triethylphosphine oxide, and the other process steps are the same. Experiments have shown that the effect of Example 3 is better than that of Example 1.
[0108] Example 4
[0109] The similarities between Example 4 and Example 2 are not repeated here. The difference between Example 4 and Example 2 is that trioctylphosphine oxide is replaced by triethylphosphine oxide, and the other process steps are the same. Experiments have shown that the effect of Example 4 is better than that of Example 2.
[0110] Test Example 1
[0111] Photoelectric performance test: The solar cells prepared in various embodiments and comparative examples were tested at a room temperature of 25° C., a humidity of 30%, and irradiation with one sun.
[0112] The test results of Example 1 are plotted as Figures 2 to 5 , Figures 2 to 5They are the statistical graphs of the battery’s open circuit voltage, current density, photoelectric conversion efficiency, and fill factor. Figures 2 to 5 It can be seen that the solar cell prepared in Example 1 of the present application has better performance in all aspects.
[0113] Test Example 2
[0114] In order to compare the effect of adding trioctylphosphine oxide, solution B and solution A were spin-coated on the same silicon wafer, and then the perovskite solution was spin-coated on the hole transport layer in turn. The perovskite solution was 50 μL and the rotation speed was consistent.
[0115] Figure 6 is the contact angle of the perovskite drop on the hole transport layer of solution B;
[0116] Figure 7 is the contact angle of the perovskite drop on the hole transport layer of solution A;
[0117] Will Figure 6 and Figure 7 By comparison, it can be seen that the contact angle of the hole transport layer of solution B is significantly smaller than that of solution A, which indicates that solution B has better wettability.
[0118] In summary, the solar cell and the method for manufacturing the same provided in the embodiments of the present application have the following characteristics:
[0119] 1. Distributing small molecules containing phosphine oxide groups, sulfone moieties or carbonyl groups in the hole transport layer so that they coordinate with lead in the perovskite light absorbing layer can enhance the binding force between the hole transport layer and the perovskite light absorbing layer, thereby enhancing the long-term stability of the solar cell; during the preparation process, since the small molecules containing phosphine oxide groups, sulfone moieties or carbonyl groups are distributed in the hole transport layer, the hydrophobicity problem of the perovskite precursor solution and the hole transport layer can be effectively improved, and the wettability of the perovskite light absorbing layer can be improved;
[0120] 2. During the preparation process, some high-boiling-point solvents are added to the hole transport layer solution to delay the drying process, which can induce the aluminum oxide groups in the film layer to achieve efficient coordination with the perovskite light-absorbing layer on the upper surface;
[0121] 3. During the preparation process, the annealing and drying method of the hole transport layer is low-temperature two-step annealing, which can further induce the phosphine oxide groups or sulfone moieties or carbonyl small molecules in the film layer to achieve efficient coordination with the perovskite light-absorbing layer;
[0122] 4. No modification layer is required between the hole transport layer and the perovskite layer, thereby reducing process steps, improving process efficiency and saving costs.
[0123] The above are only preferred embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing a solar cell, characterized in that: include: coating a hole transport layer solution on a substrate to form a hole transport layer, coating a perovskite layer solution on the hole transport layer, wherein the perovskite layer solution contains lead ions; Small molecules coordinated with the lead ions are dissolved in the hole transport layer solution.
2. The preparation method according to claim 1, characterized in that: The hole transport layer solution contains small molecules coordinated with the lead ions. Specifically, it is a small molecule containing a phosphine oxide group, a small molecule containing a sulfone group, or a small molecule containing a carbonyl group.
3. The preparation method according to claim 2, characterized in that: The small molecule containing a phosphine oxide group is selected from at least one of trimethyl phosphine oxide, triethyl phosphine oxide, tripropyl phosphine oxide, tributyl phosphine oxide, triylpentyl phosphine oxide, trihexyl phosphine oxide, triheptyl phosphine oxide, trioctyl phosphine oxide, diphenyl phosphine oxide, triphenyl phosphine oxide, ethyl diphenyl phosphine oxide, di-tert-butyl phosphine oxide and tripyrrolidine phosphine oxide.
4. The preparation method according to claim 2, characterized in that: The small molecule containing sulfone moieties is selected from at least one of butyl sulfone, diphenyl sulfone, dimethyl sulfone, butyl sulfoxide, benzyl sulfone, methyl vinyl sulfone, ethyl phenyl sulfone, phenyl vinyl sulfone, methyl phenyl sulfoxide, methyl ethyl sulfone, ethyl vinyl sulfone, dodecyl methyl sulfoxide, methyl p-toluene sulfoxide, 4-aminophenyl sulfone, bis(4-chlorophenyl) sulfone and 4,4'-ditoluene sulfoxide.
5. The preparation method according to claim 2, characterized in that: The small molecule containing a carbonyl group is selected from at least one of 1,1′-carbonyldiimidazole, 1,1′-carbonylbis(1,2,4-triazole), N-cyanocarbonyldiphenyl ester, 4-ethoxycarbonylphenylisocyanate, 2-(methoxycarbonyl)phenylisocyanate, ethoxycarbonylisothiocyanate, 1,1′-thiocarbonyldi-2(1H)-pyridone, and 1,1′-(azodicarbonyl)dipiperidine.
6. The preparation method according to claim 2, characterized in that: The small molecule containing the phosphine oxide group is triethylphosphine oxide, and the mass ratio of the triethylphosphine oxide to the hole transport layer material is 1:50-1:
5.
7. The preparation method according to any one of claims 1 to 6, characterized in that: Coating a hole transport layer solution on the substrate, and forming the hole transport layer by two-step annealing and drying; The two-step annealing method is to place the substrate coated with the hole transport layer solution at a temperature of 50-60° C. for drying for 3-5 minutes, and then place the substrate at a temperature of 100-110° C. for drying for 10-15 minutes.
8. The preparation method according to any one of claims 1 to 6, characterized in that: The solar cell is a stacked cell or a single junction cell.
9. The preparation method according to any one of claims 1 to 6, characterized in that: The hole transport layer solution includes a high boiling point solvent; The high boiling point solvent is selected from at least one of dimethylacetamide, aniline, bromobenzene, o-dichlorobenzene, butyl butyrate, PC (propylene carbonate), and E-CPL (E-caprolactone).
10. A solar cell, characterized in that: The method is as described in any one of claims 1 to 9.